Potential health hazards of existing chemicalls (Germany, 1996)
The volumes in this series present critically-assessed data and recommendations for occupational safety officers, industrial hygienists, and human and animal toxicologists. They are constantly reviewed to provide up-to-date information. This volume provides data for the following chemicals: Ammonium persulphate, p-Chloroaniline, Hydrazobenzene, Dicyclopentadiene, Butynediol, Di-2-ethylhexylamine, Tetramethylthiuram monosulphide, 7-Amino-4-hydroxy-2-naphthalenesulphonic acid, 6-Amino-4-hydroxy-2-naphthalenesulphonic acid, 4-Nitrodiphenylamine, and Acetic acid methyl ester.
Keywords: Toxicity testing,Hazardous Substances,Nghiên cứu độc tố,Chất nguy hiểm; Toxicity,Đặc tính độc